The Breeding Seasons of Birds on Timor - Richard A Noske (KUKILA, 2003)
The breeding seasons of land birds on Timor, the largest island of the Lesser Sundas (Nusa Tenggara) is hitherto undocumented. This preliminary report draws upon historic data from the early 20'h century and opportunistic observations made by the author on Timor during the 1990s, and compares these data with those available for other islands in the region (including Roti and Sumba), as well as western Indonesia and Papua. Evidence is presented that nesting occurs throughout the wet season (November to April), possibly peaking in November. This pattern contrasts strongly with that for western Flores (Verheijen 1964), where breeding is concentrated in the three months from April to June. Interpretation of these patterns must be cautious, however, given the hiatus of data from Timor for the period from late August to November, as well as the opportunistic or approximate nature of the data presented here. lt is hoped that this report stimulates a more comprehensive study of avian reproduction in the region.